An application of reflective holographic gratings for measurement of cylindrical curvature - Chanikan Inneam; Keerayoot Srinuanjan; Witoon Yindeesuk (My University, 2021)
Abstract This paper presented an application of reflective holographic gratings for the measurement of cylindrical curvature. The surface of the fabricated holographic grating was coated with gold by the sputtering method, where it became a reflective holographic grating. The grating was attached to the surface of various radius cylindrical objects. The diffraction pattern produced by the bent grating with different radius was observed by illuminating a laser beam normal to the grating surface. The gratings constant were calculated from the observed diffraction pattern. The relationship between the grating constants and the radius of cylindrical objects was obtained. The grating constant and the reciprocal of the radius of cylindrical objects was a linear relationship, with the least R-square between 0.85-0.97. Moreover, the y-intercept of the relationship between the grating constants and the reciprocal radius was consistent with the grating constant of the non-bended grating. As the radius of the grating approach is infinite, the reciprocal of the radius approaches zero, which is a non-bend grating. We can apply this method to measure the radius of cylindrical objects.
Keywords: Radius of curvature; Ultrasonic grating; Constant (computer programming); Optical Coatings and Gratings